Hubungan Sosialisasi Program BPJS Terhadap Pemahaman Tentang Hak Peserta BPJS Kesehatan Di RSUD Syarifah Ambami Rato Ebu Bangkalan - Nurfaidatil Laili (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2014)
The members’ right and obligation about healthy of BPJS is stated in BPJS rule No. I in 2014. The society’s participation in BPJS program is very significant to guarantee their healthy. So, they must understand well how to register and take care the process of BPJS services in order they can get a maximum service. This issue is being discussed by government. The research design is Cross Sectional design by two variables, those are BPJS socialization and the understanding of the BPJS members’ right. The population is 108 members and the sample is 85 members in internist Poly in Syarifah Ambami Rato Ebu Hospital Bangkalan. The Sampling technique is Non Probability with type of sampling is Incidental Sampling. The instruments is questionnaire by using statistic test that is Lambda Correlation Coefficient. The result of this research showed 55 members (65%) were never given socialization while 52 members (61%) felt less understand about the BPJS right. Based on Statistical of Lambda correlation, the p value : 0,027 < α : 0,05 which it means there was relationship between socialization toward the understanding about the members’ right in Internist Poly in Syarifah Ambami Rato Ebu Hospital Bangkalan. For the following researcher, the researcher suggests to do a research which focuses on the factors that influence the obstacles of health BPJS socialization in order the members are more comprehensive about their rights. Key words : The Understanding of BPJS members’ right, BPJS socialization